2020
DOI: 10.1088/1741-2552/abbbd6
|View full text |Cite
|
Sign up to set email alerts
|

Brain connectivity in patients with dystonia during motor tasks

Abstract: Objective. This study aims to investigate alterations of brain connectivity using multivariate electroencephalographic data to provide new insights of the brain connectivity dynamics of dystonia. Approach. We recorded electroencephalography (EEG) of patients with right upper limb idiopathic focal dystonia and paired controls during resting state, writing-from-memory, and finger-tapping tasks. We applied power spectrum analyses considering the mu, beta and gamma rhythms of the motor cortex and analyzed brain co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 46 publications
1
12
0
Order By: Relevance
“…Using independent component analysis, we found that motor tasks modulated the same networks as rest state brain in both healthy and dystonia subjects. Specifically, the sensorimotor, parietal, frontoparietal, visual, basal ganglia, and cerebellum were all modulated as previously reported (Battistella and Simonyan 2019;Mantel et al 2018;Huang et al 2017;Baltazar et al 2020). Our study also found that insular, orbitofrontal and default mode networks were also modulated during motor tasks.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Using independent component analysis, we found that motor tasks modulated the same networks as rest state brain in both healthy and dystonia subjects. Specifically, the sensorimotor, parietal, frontoparietal, visual, basal ganglia, and cerebellum were all modulated as previously reported (Battistella and Simonyan 2019;Mantel et al 2018;Huang et al 2017;Baltazar et al 2020). Our study also found that insular, orbitofrontal and default mode networks were also modulated during motor tasks.…”
Section: Discussionsupporting
confidence: 88%
“…The remaining components in this study showed a high overlap with previously identified ICN networks and anatomic regions indicating their independent validation and biological relevance. Functional networks previously shown to play a role in patients with dystonia were then selected for further analysis (Battistella and Simonyan 2019;Mantel et al 2018;Huang et al 2017;Baltazar et al 2020) and they are listed in Table 1. The components denoted as the sensorimotor cortex (SM) showed bilateral activation in the motor and sensory cortical regions, however, were denoted left and right based on which side showed more activation.…”
Section: Group Independent Component Analysis: a Group Independent Component Analysis (Gica)mentioning
confidence: 99%
See 1 more Smart Citation
“…A similar change of hub status was reported for the primary motor cortex in hand dystonia (including WC and musicians focal hand dystonia) ( 19 ). In an EEG study, WC patients exhibited disruption of intracortical inhibition during a writing-from memory task ( 39 ). While EEG does not have the spatial resolution to pinpoint this finding to the primary motor cortex, it supports the notion that inhibitory connections are impaired in WC.…”
Section: Discussionmentioning
confidence: 99%
“…Correlation between EEG channels, also known as coherence, was evaluated in time-domain to analyze the connectivity patterns in dystonia patients [1]. Coherences have the advantage of yielding the possibility to recognize motor-imagery related activation even without typical activation observed, often giving small standard deviations [13].…”
Section: Related Workmentioning
confidence: 99%